2020
DOI: 10.1002/pol.20200027
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of light scattering and haze in semicrystalline polymers

Abstract: This article reports a new model approach for the description of light scattering in semicrystalline polymers, to describe more precisely the influence of supermolecular structure on the optical properties. This is the first study in which light scattering of polymer films has been modeled using exact Mie scattering theory of radially anisotropic spheres. As a model material a well‐known polymer, isotactic polypropylene (iPP) was used. Samples were prepared with different sample thicknesses and crystalline str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…In contrast, merely insignificant influences of the monitored spectrum can be observed for the application of an insufficient energy density level, shown in Figure 10 b. With regard to the wavelength-dependent analytic modeling of light scattering in semi-crystalline polymers by Molnár et al (2020) [ 57 ], the observed wavelength dependencies can be correlated with the occurrence of Mie scattering inside the melt pool. Therefore, wavelength-dependent deviations are associated with varying concentrations and geometries of spherulites, defects and pores inside the melt pool.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, merely insignificant influences of the monitored spectrum can be observed for the application of an insufficient energy density level, shown in Figure 10 b. With regard to the wavelength-dependent analytic modeling of light scattering in semi-crystalline polymers by Molnár et al (2020) [ 57 ], the observed wavelength dependencies can be correlated with the occurrence of Mie scattering inside the melt pool. Therefore, wavelength-dependent deviations are associated with varying concentrations and geometries of spherulites, defects and pores inside the melt pool.…”
Section: Resultsmentioning
confidence: 93%
“…As the crystallinity in the structure increase, the density increase resulting in a slower speed of light traveling through the structure. The amount of light transmitted through the material also depends on the thickness, therefore many thin polymers depict high transparency [17]. PVDF is a semicrystalline polymer with crystallinity ranging from 35%-70% depending on the polymerization method.…”
Section: Resultsmentioning
confidence: 99%
“…Normalized transmission plotted in figure 3 is a ratio of light transmitted through and total light incident on the material. The amount of light attenuated due to scattering in the material is measured by the scattering attenuation parameter (α s ) [17]. This parameter (α s ) is mathematically calculated by the product of nucleus density (n o ), and extinction cross-section (C ext ).…”
Section: Resultsmentioning
confidence: 99%
“…By encapsulating the VO 2 nanocrystals in a SiO 2 shell with an intermediate refractive index of ca. 1.8, light scattering at the discontinuous filler/laminate-matrix interface is greatly alleviated. ,, In the absence of a dispersing agent, hydrophilic VO 2 @SiO 2 nanoparticles remain somewhat agglomerated even upon shear mixing, which gives rise to Mie scattering that degrades the optical clarity of the films. ,, The importance of the coupling agent is readily apparent in Figure A, where the use of surface functionalization suppresses haze and increases the visible light transmittance from ∼26.9% to 47.6%. Contrasting VO 2 @SiO 2 nanocomposite fenestration elements with different extents of functionalization for the same overall active filler loading (0.8 mg/mL), functionalization with 6.1 wt % is found to be optimal, yielding NIR modulation of 22.3% and T 555nm of 47.6%.…”
Section: Resultsmentioning
confidence: 99%